(untitled) (Communication & Society, 2021)
The aim of this paper is to explore the political messages painted on Madrid’s walls by urban artists from the beginning of this artistic and political movement (the end of the 1990s) to the present day. We developed an extensive field-work that has helped us to create the first compilation of the key political messages of urban art in Madrid, based on an exploratory research approach complemented by the use of social media search. This descriptive and documentary approach was followed while keeping in mind that a wall is a public channel open to all and an outstanding method for expressing any political opinion with the greatest amount of visibility. Over the time span analyzed, the investigation discovered 15 urban artists with political content in their artistic production. The findings indicate that the political theme of these artists’ works focuses primarily on condemning the Spanish government for current issues such as corruption or the economic crisis, as well as past events such as the Iraq War. Other recurring themes include social criticism of municipal policies and the living conditions of underprivileged groups such as refugees and beggars, as well as support for feminism and critiques of the rapid gentrification process of certain historic Madrid neighborhoods, such as Malasaña and Lavapiés.